Diffraction gratings and applications - Loewen, Erwin G. (Optical engineering (Marcel Dekker, Inc.), 1997)
Offers and up-to-date assessment of the entire field of diffraction gratings, including history, physics, manufacture, testing, and instrument design. Furnishes--for the first time in a single-source reference--a thorough review of efficiency behavior, examining echelles as well as concave, binary, transmission, fiber, and waveguide gratings.